The Criminology Portrayed In Taken (2008) Movie Script - Elfrina Elfrina; Rezki Amalia Wahyuni Mustakim; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2025)
The study examined the representation of human trafficking in the movie Taken (2008) and its impact on public perception. Utilizing a qualitative approach, data was gathered through script analysis and interviews with 30 informed respondents, based on Maggy Lee's theory of human trafficking, Aristotle's rhetoric, and Chernobrov's insights on public perception. Findings indicate that Taken portrays various forms of human trafficking, including modern slavery and sexual exploitation, while also highlighting the connections between organized crime and migration. The character Peter employs rhetorical strategies to build trust and manipulate victims, illustrating the complexities of victimization. Although the movie raises awareness about human trafficking, it inadequately represents the psychological trauma experienced by victims. The results provide insights into how cinematic portrayals influence public understanding of human trafficking and shape societal attitudes. The analysis underscores the intricate relationship between media narratives and public perception, revealing how the Taken informs audiences about a critical social issue while also exposing its limitations in depicting the full scope of victim experiences. By focusing on these aspects, the study contributes to a deeper understanding of the impact of popular media on societal views regarding human trafficking.